Parecoxib as an adjunct therapy for the treatment of refractory non-surgical cancer pain. (September 2020) - Thakerar, Arti; Dines-Muntaner, Seamus; Trifunovich, Tijana; Alexander, Marliese; Fullerton, Sonia
Background: Evidence for the use of short-term daily parenteral parecoxib for refractory or uncontrolled non-surgical cancer pain is limited. This study aimed to characterise the real-world off-label use and report on clinical experiences in an Australian cancer cohort. Methods: Eligible patients received at least one dose of parecoxib of an intended three-day course between October 2015 and December 2018. Data were collected to characterise the parecoxib treatment cohort (cancer diagnosis, metastases, sites and types of pain and prior analgesia). Parecoxib-related adverse events, pain scores (worst and median), and concurrent opioid use were assessed at 24 h pre (T0) and 24 (T1), 48 (T2), 72 (T3) and 96 h (T4) post first parecoxib dose. Results: Sixty-five patients (39 males and 26 females) and 68 courses of parecoxib (three patients treated twice) were included in analyses: metastatic disease (86%), bone pain (54%) and taking ≥3 classes of analgesic medications (69%). Pain types varied (46% non-specific, 22% neuropathic and 32% other). Most (94%) received parecoxib by subcutaneous administration. Following parecoxib, median 24-h pain scores and worst pain scores improved for 59% (40/68) and 50% (34/68) of patients, respectively. In the first 24 h (T0 to T1), median (4 vs. 2, p < 0.01) and worst (6 vs. 5, p < 0.01) pain scores were reduced and sustained to T4 (4 vs. 2.5, p = 0.01). Breakthrough analgesia requirements reduced for 63% (43/68) of patients, while total concurrent opioid use remained constant. Mean/median oral morphine equivalence for T0 vs. T1 was 111 mg/75 mg vs. 162 mg/90 mg, (p > 0.8). Two patients ceased parecoxib due to renal/liver function abnormalities and two experienced mild injection-site reactions. Conclusions: In this real-world study, parecoxib was utilised as adjunctive therapy in a select patient cohort to contribute to reduced pain scores with no new safety signals. Prospective randomised studies in larger cohorts would improve understanding of the effects of parecoxib.